The Effectiveness of Health Education using Mobile Phone-based Audiovisual on Knowledge and Attitude among Mother in Treating Toddler with Pneumonia - La Saudi; Nani Nurhaeni; Happy Hayati (Alta Dharma Publisher, 2020)
Mothers who have good knowledge will support the acceleration of pneumonia recovery of toddlers. The study aimed to examine the effectiveness of mobile phone-based audiovisual education on increasing knowledge and attitudes among mothers in treating toddlers with pneumonia. The quasi-experimental study, pre-test, and post-test design with the non-equivalent control group were applied in this study. Forty-six samples collected using consecutive sampling with questionnaires analyzed by the Fisher Exact Test. There are differences in the knowledge and attitudes of mothers in the intervention group before and after health education (knowledge: p= 0.017; attitude: p= 0.003). But in the control group, it is only knowledge that is significantly different (p= 0.030). Knowledge and attitudes in the intervention and control groups have different statistical values ??after health education (knowledge: p= 0.018; attitude: p= 0.384). Conclusion: There is a correlation between education and experience with knowledge of mothers in treating toddlers with pneumonia, but there is no difference in mothers' attitudes. Concerning age, family income, and information, there is no difference in mothers' knowledge and attitudes. Using audiovisuals in health education activities to improve mothers' knowledge and attitudes